2021
DOI: 10.3389/fphar.2021.609817
|View full text |Cite
|
Sign up to set email alerts
|

3′-Sialyllactose Protects SW1353 Chondrocytic Cells From Interleukin-1β-Induced Oxidative Stress and Inflammation

Abstract: Osteoarthritis (OA) is a major degenerative joint disease. Oxidative stress and inflammation play key roles in the pathogenesis of OA. 3′-Sialyllactose (3′-SL) is derived from human milk and is known to regulate a variety of biological functions related to immune homeostasis. This study aimed to investigate the therapeutic mechanisms of 3′-SL in interleukin-1β (IL-1β)-treated SW1353 chondrocytic cells. 3′-SL potently suppressed IL-1β-induced oxidative stress by increasing the levels of enzymatic antioxidants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Sialylated HMOs account for approximately 13% of total HMOs, in which 3′-sialyllactose (3′-SL), a representative and simplest one, is present at approximately 2%. , 3′-SL, structurally represented as Neu5Acα2,3Galβ1,4Glc, consists of N -acetylneuraminic acid (Neu5Ac) and lactose units. It has been widely confirmed to display promising prebiotic effects, antiadhesive antimicrobials, antiviral activity, preventing necrotizing enterocolitis (NEC), immunomodulatory, modulating intestinal epithelial cell response, and promoting brain development and improving cognition . The safety evaluation of 3′-SL has been widely studied in piglets, rats, and healthy humans.…”
Section: Introductionmentioning
confidence: 99%
“…Sialylated HMOs account for approximately 13% of total HMOs, in which 3′-sialyllactose (3′-SL), a representative and simplest one, is present at approximately 2%. , 3′-SL, structurally represented as Neu5Acα2,3Galβ1,4Glc, consists of N -acetylneuraminic acid (Neu5Ac) and lactose units. It has been widely confirmed to display promising prebiotic effects, antiadhesive antimicrobials, antiviral activity, preventing necrotizing enterocolitis (NEC), immunomodulatory, modulating intestinal epithelial cell response, and promoting brain development and improving cognition . The safety evaluation of 3′-SL has been widely studied in piglets, rats, and healthy humans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was a greater decrease in the expression of M1 and M2 specific markers in the 3' SL treatment group compared to the control group. Together, IL-1β induce osteoarthritic pathogenesis by oxidative stress and inflammation but 3'-Sialyllactose can suppress of oxidative stress and inflammation [27]. Thus, we demonstrated that 3' SL maintains the state of resting macrophages and protects from LPS-induced inflammation.…”
Section: Discussionmentioning
confidence: 65%
“…HMOs also play important roles in regulating neonatal intestinal immunity, resisting viral , and bacterial infections, reducing anti-inflammatory responses, and promoting brain development . These functions are related to their structures to a certain extent, but to date, a comprehensive summary of the structure–function relationships of different types of HMOs has not been published.…”
Section: Structure–function Relationships Of Hmosmentioning
confidence: 99%
“…For example, Baek et al. found that 3′-SL inhibited MAPK and PI3K/AKT/NF-κB signaling and downregulated oxidative stress and inflammation to alleviate IL-1β-induced osteoarthritis (OA) pathogenesis in a dose-dependent manner . Holscher et al constructed an intestinal epithelial cell model using HT-29 cells and Caco-2Bbe cells and explored the effect of three HMOs (2′-FL, 6′-SL, and LNnT) on intestinal cell maturation.…”
Section: Dose-dependent Effects Of Hmosmentioning
confidence: 99%